Predictors of dynamic hyperinﬂation during the 6-minute walk test in stable chronic obstructive pulmonary disease patients - Chen, Rui; Lin, Lin; Tian, Jing-Wei; Zeng, Bin; Zhang, Lei; Chen, Xin; Yan, Hai-Yan (Journal of Thoracic Disease; Vol 7, No 7 (July 30, 2015): Journal of Thoracic Disease, 2015)
Background: Dynamic hyperinflation (DH) is a major contributor to exercise limitation in chronic obstructive pulmonary disease (COPD). Therefore, we aimed to elucidate the physiological factors responsible for DH development during the 6-minute walk test (6MWT) in COPD patients and compare ventilatory response to the 6MWT in hyperinflators and non-hyperinflators. Methods: A total of 105 consecutive subjects with stable COPD underwent a 6MWT, and the Borg dyspnea scale, oxygen saturation (SpO2), breathing pattern, and inspiratory capacity (IC) were recorded before and immediately after walking. The change in IC was measured, and subjects were divided into hyperinflators (ΔIC >0.0 L) and non-hyperinflators (ΔIC ≤0.0 L). Spirometry, the Modified Medical Research Council (MMRC) dyspnea scale and St George’s Respiratory Questionnaire (SGRQ) were also assessed. Results: DH was present in 66.67% of subjects. ΔIC/IC was significantly and negatively correlated with the small airway function. On multiple stepwise regression analysis forced expiratory flow after exhaling 50% of the forced vital capacity (FEF50%) was the only predictor of ΔIC/IC. Non-hyperinflators had a higher post-walking VT (t=2.419, P=0.017) and post-walking VE (t=2.599, P=0.011) than the hyperinflators did. Age and resting IC were independent predictors of the 6-minute walk distance (6MWD) in hyperinflators. Conclusions: DH was considerably common in subjects with COPD. Small airway function may partly contribute to the DH severity during walking. The ventilator response to the 6MWT differed between hyperinflators and non-hyperinflators. Resting hyperinflation is an important predictor of functional exercise capacity in hyperinflators.